Implementation of Chest Physiotherapy and Effective Coughing on Respiratory Disorders In Patients With COVID-19: A Case Study - Syarif Jafar Sidiq; Rina Puspita Sari (Indonesian Journal of Community Development, 2022)
COVID-19 can cause symptoms of acute respiratory disorders such as fever above 38°C, cough, and shortness of breath for humans. One of the nursing interventions that can be applied to clear the sputum in the airway is chest physiotherapy and effective coughing. The research design used an evaluative design is a case study with data analysis using descriptive-analytic. The case study was carried out on adults, 57 years old with Covid-19. Chest physiotherapy and cough intervention were given for 7 days. the results obtained after this action that the client does not complain of shortness of breath again and coughs are not felt again. These nursing actions can be taken to reduce the symptoms of respiratory disorders felt in patients with Covid-19